THE EFFECTIVENESS OF DIARY WRITING AS A MEDIUM TO IMPROVE STUDENTS’ MASTERY OF SIMPLE PAST TENSE AT SMPN 15 MAKASSAR - Asis, Alya Difa; Muliati, A.; Muhayyang, Maemuna (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This study aims to test the effectiveness of using Diary Writing to improve students’ mastery of the Simple Past Tense at SMPN 15 Makassar. It consists of 8 classes and the total population is 216 students. Participants were randomly selected using the random sampling technique, the researcher chose 1 class from 8 classes randomly. The research employed a pre-experimental approach with pre-tests and post-tests. Thirty-one students significantly increased from a pre-test mean score of 33.87 to 87.10 in the post-test. By conducting a paired-sample t-test statistical analysis with a significance level set at α = 0.05, a significant difference between the mean scores of the pre-test and post-test was found (p <0.05) the research supports the hypothesis that employing diary writing effectively enhances the understanding of the Simple Past Tense. These findings underscore the value of using writing diaries as an engaging media for English educators teaching the Simple Past Tense.